Developing and Evaluating the Concept Data Awareness for K12 Computing Education - Höper, Lukas (21st Koli Calling International Conference on Computing Education Research)
Students often have a lack of understanding and awareness of where, how, and why personal data about them is collected and processed. Especially, when interacting with data-driven digital artifacts, an appropriate perception of the data collection and processing is necessary for self-determination. This dissertation deals with the development and evaluation of a concept called data awareness which aims to foster students’ self-determination interacting with data-driven digital artifacts.
Keywords: data awareness; machine learning; data science education; data-driven digital artifacts; artificial intelligence

Development of Methods for Coil-Based Localization by Magnetic Fields of Miniaturized Sensor Platforms in Bioprocesses - Lange, Sven; Schröder, Dominik; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (22nd IEEE International Conference on Industrial Technology (ICIT))
In this publication important aspects for the implementation of inductive locating are explained. The miniaturized sensor platform called Sens-o-Spheres is used as an application of this locating method. The sensor platform is applied in bioreactors in order to obtain the environmental parameters, which makes a localization by magnetic fields necessary. Since the properties of magnetic fields in the localization area are very different from the wave characteristics, the principle of inductive localization is investigated in this publication and explained by using electrical equivalent circuit diagrams. Thereby, inductive localization uses the coupling or the mutual inductivities between coils, which is noticeable by an induced voltage. Therefore some properties and procedures are explained to extract the location of Sens-o-Spheres or other industrial sensor platforms from the couplings of the coils. One method calculates the location from an adapted ratio calculation and the other method uses neural networks and stochastic filters to obtain the results. In the end, these results are evaluated and compared.
Keywords: Location awareness; Coils; Couplings; Nonuniform electric fields; Magnetic separation; Neural networks; Training data

Welcome back to school: Aussprache in Klasse 5 prüfen - Bredenbröcker, Martina; Hahn, Charlotte Anna (Englisch 5 - 10)
Keywords: Abschlussprüfung Englisch; Auslautverhärtung; Aussprache; awareness raising activities; final-obstruent devoicing; Lautschulung; oral exam; pronunciation; silent letters; th; w vs. v

Computational self-awareness as design approach for visual sensor nodes - Guettatfi, Zakarya; Hübner, Philipp; Platzner, Marco; Rinner, Bernhard (12th International Symposium on Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC))
Keywords: embedded systems; image sensors; power aware computing; wireless sensor networks; Zynq-based VSN node prototype; computational self-awareness; design approach; platform levels; power consumption; visual sensor networks; visual sensor nodes; Cameras; Hardware; Middleware; Multicore processing; Operating systems; Runtime; Reconfigurable platforms; distributed embedded systems; performance-resource trade-off; self-awareness; visual sensor nodes

Self-Aware and Self-Expressive Systems – Guest Editor's Introduction - Torresen, Jim; Plessl, Christian; Yao, Xin (IEEE Computer)
Keywords: self-awareness; self-expression

Conceptualizing pronunciation as part of translingual/transcultural competence: New impulses for SLA research and the L2 classroom - Müller, Mareike (Foreign Language Annals)
This article aims to reconceptualize pronunciation teaching and learning according to the tenets of the 2007 MLA Report and its call for translingual/transcultural competence. The critical discussion of current teaching and research practices shows that the realm of pronunciation has benefitted little from debates on intercultural language learning. In order to link the teaching of pronunciation with learner needs in intercultural encounters, this article develops the concept of pronunciation‐as‐language. The theoretical exploration of this concept is supported by a narrative analysis of study-abroad learners’ accounts, contrasting learners’ perceptions of teaching practices with the complex role pronunciation plays in second language‐mediated interactions. The results underline the importance of pedagogical approaches that encourage the critical reflection on and creative use of pronunciation beyond structural elements and native‐speaker norms.
Keywords: critical language awareness; native‐speaker ideal; pronunciation; study abroad; translingual and transcultural competence

Top-down contingent feature-specific orienting with and without awareness of the visual input. - Ansorge, Ulrich; Horstmann, Gernot; Scharlau, Ingrid (Advances in Cognitive Psychology)
In the present article, the role of endogenous feature-specific orienting for conscious and unconscious vision is reviewed. We start with an overview of orienting. We proceed with a review of masking research, and the definition of the criteria of experimental protocols that demonstrate endogenous and exogenous orienting, respectively. Against this background of criteria, we assess studies of unconscious orienting and come to the conclusion that so far studies of unconscious orienting demonstrated endogenous feature-specific orienting. The review closes with a discussion of the role of unconscious orienting in action control. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual input; awareness; conscious; orientation; visual perception; Awareness; Consciousness States; Perceptual Orientation; Visual Perception; Blindsight

Enhancing implicit change detection through action. - Tseng, Philip; Tuennermann, Jan; Roker-Knight, Nancy; Winter, Dorina; Scharlau, Ingrid; Bridgeman, Bruce (Perception)
Implicit change detection demonstrates how the visual system can benefit from stored information that is not immediately available to conscious awareness. We investigated the role of motor action in this context. In the first two experiments, using a one-shot implicit change detection paradigm, participants responded to unperceived changes either with an action (jabbing the screen at the guessed location of a change) or with words (verbal report), and sat either 60 cm or 300 cm (with a laser pointer) away from the display. Our observers guessed the locations of changes at a reachable distance better with an action than with a verbal judgment. At 300 cm, beyond reach, the motor advantage disappeared. In experiment 3, this advantage was also unavailable when participants sat at a reachable distance but responded with hand-held laser pointers near their bodies. We conclude that a motor system specialized for real-time visually guided behavior has access to additional visual information.
Keywords: implicit change detection; action perception; visual system; perceptual judgment; verbal fluency; Analysis of Variance; Awareness; Female; Humans; Male; Psychomotor Performance; Random Allocation; Reaction Time; Visual Perception; Visual Memory; Visual Stimulation; Implicit Memory; Judgment; Perceptual Discrimination

Influences of visibility, intentions, and probability in a peripheral cuing task. - Ansorge, Ulrich; Heumann, Manfred; Scharlau, Ingrid (Consciousness and Cognition: An International Journal)
According to the concept of direct parameter specification, nonconsciously registered information can be processed to the extent that it matches currently active intentions of a person. This prediction was tested and confirmed in the current study. Masked visual information provided by peripheral cues led to reaction time (RT) effects only if the information specified one of the required responses (Experiments 1 and 3). Information delivered by the same masked cues that did not match the intentions was not used. However, the same information influenced RT if it was provided by visible cues (Experiments 2 and 3). The results suggest that the processing of nonconsciously registered information is flexible because it is susceptible to the changing intentions of a person. Yet, these processes are apparently restricted as nonconsciously registered information cannot be used as easily for purposes not corresponding to the currently active intentions as better visible information. (PsycINFO
Keywords: active intentions; cues; direct parameter specification; nonconscious processing ability; Adult; Consciousness; Female; Humans; Male; Mental Processes; Perceptual Masking; Photic Stimulation; Visual Perception; Awareness; Cognitive Processes; Cues; Intention; Consciousness States; Probability